At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
5 (y - 6) = 3 (y - 4) :First, distribute on both sides.
5y - 30 = 3y - 12 :Then, add the 30 over to the 12.
+30 +30
5y = 3y + 18 :Next, subtract the 3y over to the 5y.
-3y -3y
(2y = 18) ÷ 2 :Then, divide the whole equation by 2
Your final answer is:
y = 9
5y - 30 = 3y - 12 :Then, add the 30 over to the 12.
+30 +30
5y = 3y + 18 :Next, subtract the 3y over to the 5y.
-3y -3y
(2y = 18) ÷ 2 :Then, divide the whole equation by 2
Your final answer is:
y = 9
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.